Resistance profile of Escherichia coli strains in micro-basins with different soil use and occupation, in the Northwest of Rio Grande do Sul, Brazil - Ubiratan Alegransi Bones; Genesio Mario da Rosa; Kauane Andressa Flach; Jefferson Alves da Costa Junior; Nelson Emanoel Freitas Endres (Revista Brasileira de Ciências Ambientais)
Escherichia coli, a highly adaptive microorganism, has gained scientific interest due to its rapid mutation and resistance to antimicrobial treatments. The primary sources that contribute to its rapid spread and the emergence of infections remain hotly debated. Thus, the objective of this research was to provide a baseline, as the first study in the region that analyzes the microbiological quality of water in micro-basins with different characteristics of land use and occupation. Intending to identify whether there is resistance in the isolated strains of E. coli and what their possible origins are, the study provides a behavior modeling of the studied area. To this end, three sampling campaigns were carried out, from which these microorganisms were isolated and identified by polymerase chain reaction, and were subsequently subjected to susceptibility tests with nine antibacterials widely used in the treatment of infections caused by this bacterial species. Theresultsrevealed that the watershed receiving urban sanitary effluents presented the highest contamination levels, with persistent multidrug-resistant strains throughout the collection period. Among all strains, 80% were resistant to ampicillin, while 33.3% showed resistance to cefazolin. Levofloxacinwas the most effective antibiotic, with 100% susceptibility. Micro-basins with predominant agricultural and pasture activities demonstrated less resistance than urban-impacted areas. Thishighlights the urgent need for constant monitoring and further studies to uncover the main determinants of this urgent ecological and public health problem.